Appropriate geometrical factors for four-probe method to evaluate electrical resistivity of concrete specimens. (17th April 2023) - Minagawa, H.; Miyamoto, S.; Kurashige, I.; Hisada, M.
Highlights: Appropriate geometrical factors are needed to accurately measure the electrical resistivity by the four-probe method. This paper derives appropriate geometrical factors for several types of concrete specimens. This paper introduces formulas for selecting the geometrical factor. The shape and dimensions of the specimen and the probe spacing affect the potential distribution in concrete specimens. The probe spacing must be as wide as possible to measure the mean value of the electrical resistivity of concrete. Abstract: This study computes appropriate geometrical factors for the four-probe method to accurately evaluate the electrical resistivity of concrete specimens. The geometrical factors were obtained using the potential and current distributions in the specimens calculated by finite element method analyses adopting the Laplace equation, assuming a probe spacing of 1–9 cm for several types of specimens. Furthermore, a thorough discussion of the current distribution and the variation in the measurement results indicated that the probe spacing must be as wide as possible to evaluate the mean value of the electrical resistivity.